Regional variations in the extent and pattern of grey matter demyelination in multiple sclerosis: a comparison between the cerebral cortex, cerebellar cortex, deep grey matter nuclei and the spinal cord. Issue 2 (1st October 2008) - Gilmore, C P; Donaldson, I; Bö, L; Owens, T; Lowe, J; Evangelou, N
Abstract : Background: Substantial grey matter (GM) demyelination occurs in both the cerebral cortex and spinal cord in multiple sclerosis (MS). GM demyelination also occurs in the cerebellar cortex and the deep GM nuclei of the brain. However, no study has made a direct "within subject" comparison of the extent of GM pathology between these regions. Aim: To examine the extent and pattern of GM demyelination in the motor cortex, cingulate gyrus, cerebellum, thalamus and spinal cord in MS. Methods: Postmortem study using material from 14 MS cases and three controls. Sections were taken from the five predetermined areas and stained for proteolipid protein. The extent of GM and white matter (WM) demyelination was assessed in each region. Results and conclusion: Overall, 28.8% of the GM was demyelinated compared with 15.6% of the WM (p<0.001), with demyelination being greater in the GM than in the WM at each of the anatomical sites. There was substantial variation in the extent of demyelination between the different CNS regions. GM demyelination was most extensive in the spinal cord and cerebellum while WM demyelination was most prominent in the spinal cord.